JUAL BELI ONLINE MENURUT PERSPEKTIF ULAMA FIKIH MAJENE - Sukmawati, Sukmawati (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2022)
The development of information technology and telecommunications is growing rapidly over time so that people's lifestyles also go hand in hand with the development of increasingly sophisticated technology causing people to follow a modern lifestyle, where people can make buying and selling transactions that used to occur in markets and supermarkets and until now buying and selling have appeared in the form of online buying and selling transactions using mobile phones and network assistance. internet. This research aims to examine the advantages and disadvantages of buying and selling online and find the perspective of Majene Regency scholars about buying and selling online. This type of research is qualitative research. Data analysis is done by trying to describe the data that was collected, and from the data drawn conclusions. This research was conducted in the district of Banggae Majene Regency and the speaker is a fiqh scholar domiciled in Banggae Subdistrict or works in one of the Agencies located in Majene Regency. The results of the research obtained that based on the perspective of the scholars of Banggae District Majene about online buying and selling, that the scholars of Banggae District of Majene Regency argue that online buying and selling is valid or allowed as long as it runs in accordance with the rules of sale and selling online. Buy in Islam and do not have elements that can cancel a transaction to buy and sell according to Islam.